2016
DOI: 10.1002/chem.201603366
|View full text |Cite
|
Sign up to set email alerts
|

The Copper(II)‐Catalyzed Oxidation of Glutathione

Abstract: The kinetics and mechanisms of the copper(II)-catalyzed GSH (glutathione) oxidation are examined in the light of its biological importance and in the use of blood and/or saliva samples for GSH monitoring. The rates of the free thiol consumption were measured spectrophotometrically by reaction with DTNB (5,5'-dithiobis-(2-nitrobenzoic acid)), showing that GSH is not auto-oxidized by oxygen in the absence of a catalyst. In the presence of Cu , reactions with two timescales were observed. The first step (short ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 30 publications
10
79
0
Order By: Relevance
“…It indicates that they inherit the potent GSH scavenging capability from copper(II). [ 27 ] Therefore, both nanoscale mesoporous rod‐like and cube‐like Cu‐MOFs are successfully synthesized and found to be promising GSH‐responsive and GSH‐depletion drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that they inherit the potent GSH scavenging capability from copper(II). [ 27 ] Therefore, both nanoscale mesoporous rod‐like and cube‐like Cu‐MOFs are successfully synthesized and found to be promising GSH‐responsive and GSH‐depletion drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Under Mn deplete conditions, mntABC is expressed and Cu(II) enters S. aureus cells by a MntABC-dependent mechanism. Once inside, cellular reductants reduce Cu(II) to Cu(I) (Ngamchuea et al, 2016;Rigo et al, 2004;Scarpa et al, 1996). The Cu(I) can associate with the CsoR transcriptional repressor resulting in derepression of the copAZ and copBL operons (Grossoehme et al, 2011;Rosario-Cruz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At this high concentration of EDTA, it has been reported that oxidation of GSH to GSSG in nonbiological media does not occur within 3 hours with the experimental errors of less than ±2%. 30 The reference GSH:GSSG ratio in the solution can therefore be taken from the concentrations of GSH and GSSG used to prepare the solution. The ratios of GSH:GSSG measured using the assay are 98.7 ± 1.3 % of the actual ratios of GSH:GSSG in the solutions, as displayed as a scattered plot in Figure 1c, evidencing the high accuracy of the developed assay.…”
Section: Gssg Assay)mentioning
confidence: 99%